Approche compréhensive de la tricherie en milieu scolaire : la parole aux lycéens tricheurs - Quentin Magogeat (Recherches en Éducation)
Academic cheating in France is a phenomenon that has been only conducted by a few studies. Therefore, to compensate the lack of research in this particular field, it seemed relevant to lead a comprehensive study on those future students who currently are high school pupils. In that way, this study allows high school pupils who admitted cheating to explain the reason why they act the way they do. Based on thorough interviews, the investigation reveals a series of reasons and explanations. Besides, cheating at school appears to be an identity construction process for those pupils as well as a way for them to develop specific skills. In addition to this, the study also focuses on the ethical dimension of their behavior by inspecting for instance their ability not to feel any sense of guilt.